Smoking-related DNA adducts as potential diagnostic markers of lung cancer: new perspectives - Grigoryeva, E.S.; Kokova, D.A.; Gratchev, A.N.; Cherdyntsev, E.S.; Buldakov, M.A.; Kzhyshkowska, J.G.; Cherdyntseva, N.V. (Experimental Oncology, 2015)
In recent years, the new direction such as identification of informative circulating markers reflecting molecular genetic changes in the DNA of tumor cells was actively developed. Smoking-related DNA adducts are very promising research area, since they indicate high pathogenetic importance in the lung carcinogenesis and can be identified in biological samples with high accuracy and reliability using highly sensitive mass spectrometry methods (TOF/TOF, TOF/MS, MS/MS). The appearance of DNA adducts in blood or tissues is the result of the interaction of carcinogenic factors, such as tobacco constituents, and the body reaction which is determined by individual characteristics of metabolic and repair systems. So, DNA adducts may be considered as a cumulative mirror of heterogeneous response of different individuals to smoking carcinogens, which finally could determine the risk for lung cancer. This review is devoted to analysis of the role of DNA adducts in lung carcinogenesis in order to demonstrate their usefulness as cancer associated markers. Currently, there are some serious limitations impeding the widespread use of DNA adducts as cancer biomarkers, due to failure of standardization of mass spectrometry analysis in order to correctly measure the adduct level in each individual. However, it is known that all DNA adducts are immunogenic, their accumulation over some threshold concentration leads to the appearance of long-living autoantibodies. Thus, detection of an informative pattern of autoantibodies against DNA adducts using innovative multiplex ELISA immunoassay may be a promising approach to find lung cancer at an early stage in high-risk groups (smokers, manufacturing workers, urban dwellers). Key Words: lung cancer, DNA adducts, tobacco smoking.